2017
DOI: 10.1007/s10955-017-1739-5
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating Thermal Boundary Layers and Heat Transfer in Turbulent Rayleigh–Bénard Convection

Abstract: We investigate the effect of fluctuations in thermal boundary layer on heat transfer in turbulent Rayleigh-Bénard convection for Prandtl number greater than one in the regime where the thermal dissipation rate is dominated by boundary layer contribution and in the presence of a large-scale circulating flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
1
12
1
1
Order By: Relevance
“…with e = 2π/(3 √ 3) ≈ 1.2 as well as for c = 2: (47) and (48) are found to be in good agreement with DNS results for Pr = 4.38 and Pr = 2547.9 respectively, as reported in [37]. For intermediate values of Pr between 4.38 and 2547.9, (45) with a fitted value of c is shown to be in good agreement with DNS results [42].…”
Section: Theoretical Modelsupporting
confidence: 83%
See 2 more Smart Citations
“…with e = 2π/(3 √ 3) ≈ 1.2 as well as for c = 2: (47) and (48) are found to be in good agreement with DNS results for Pr = 4.38 and Pr = 2547.9 respectively, as reported in [37]. For intermediate values of Pr between 4.38 and 2547.9, (45) with a fitted value of c is shown to be in good agreement with DNS results [42].…”
Section: Theoretical Modelsupporting
confidence: 83%
“…In [37,42] we have shown that (45) describes the temperature profiles obtained in DNS of RBC very well in the large-Pr regime, from Pr = 4.38 to Pr = 2547.9. The DNS simulations were conducted in a cylindrical container with a diameter-to-height aspect ratio 1, using the finite-volume computational code Goldfish [43].…”
Section: Validation Of the Modelmentioning
confidence: 82%
See 1 more Smart Citation
“…In particular, the value of θ ′ (0) [φ ′ (ξ)] −1/2 is a pure constant. This together with(18) immediately imply the following scaling relation for the Nusselt number with the Reynolds and the Prandtl numbers, which thus in general holds for natural boundary-layer dominated large-Prandtl-number thermal convection:Nu ∼ Re 1/2 Pr 1/2 . (20)Note that apart from RBC, the scaling(20) was found also in other different configurations of natural large-Prandtl-number thermal convective flows, for example, in horizontal convection, where the fluid layer is heated through one region of the bottom and cooled through another region of the bottom [23-25] and also in vertical convection, where the fluid is heated through one vertical surface of the fluid layer and cooled though another vertical surface…”
mentioning
confidence: 78%
“…[6,16]. This approach can be generalized to include the influence of the turbulent fluctuations within the BL [17][18][19] and also can be adapted to the case of a non-vanishing pressure gradient within the BL (or to the case of a non-constant wind above the horizontal isothermal plate, which approaches the plate at arbitrary angle), see [20,21].…”
Section: Driven) Boundary-layer Dominated Thermal Convectionmentioning
confidence: 99%